Training secondary school teachers on early attachment trauma and adolescent brain development: impact on empathy. Issue 4 (4th July 2022) - Little, Stephanie; Maunder, Rachel
ABSTRACT: This small-scale study investigated the impact of training teachers on early attachment and adolescent neuroscience. The aim was to assess change in empathy pre and post training. Forty secondary school teachers in England completed the Empathy Components Questionnaire before and after Attachment Awareness training, showing small but non-significant changes in empathy post-training. Qualitative interviews with four staff showed a positive response to the training, and changes to teachers' cognitive appraisal of pupils' challenging behaviour. However, barriers to implementation were identified with some negative reactions from staff. This provides an avenue for future research exploring how Attachment Awareness training can be implemented in schools to improve outcomes for adolescents.